How the radical right has changed capitalism and welfare in Europe and the USA - Rathgeb, Philip, 1987- 1987- (Oxford University Press, 2024)
"Radical right parties are no longer political challengers on the fringes of party systems; they have become part of the political mainstream across the Western world. This book shows how they have used their political power to reform economic and social policies in Continental Europe, Northern Europe, Eastern Europe, and the USA. In doing so, it argues that the radical right's core ideology of nativism and authoritarianism informs their socio-economic policy preferences. However, diverse welfare state contexts mediate their socio-economic policy impact along regime-specific lines, leading to variations of trade protectionism, economic nationalism, traditional familialism, labour market dualism, and welfare chauvinism. The radical right has used the diverse policy instruments available within their political-economic arrangements to protect threatened labour market insiders and male breadwinners from decline, while creating a racialized and gendered precariat at the same time."